Pengaruh Cause-Related Marketing terhadap Minat Beli Buku Lekas Sembuh pada Generasi Z di Yogyakarta dan Bandung - Muhammad Hisyam Syafii; Halim Purnomo (MAMEN: Jurnal Manajemen, 2024)
This study aims to investigate the influence of Cause-Related Marketing (CRM) on the level of consumer buying interest in the book "Get Well Soon" in Yogyakarta and Bandung, especially in generation Z. Data was collected from 152 respondents via an online survey, and analysis was carried out using Linear Regression techniques and Chi-Square. The research results show that there is a significant relationship of 0.000<0.05 between CRM and the level of consumer buying interest in the book "Get Well Soon". These findings emphasize the importance of marketing strategies that focus on company/product involvement in social or humanitarian issues in influencing consumer behavior. Based on research results which show a significant relationship between Cause-Related Marketing (CRM) and the level of consumer buying interest in the book "Get Well Soon", it can be concluded that marketing strategies that focus on company involvement in social or humanitarian issues have an important impact in influencing consumer behavior. These findings support the Cause-Related Marketing theory which shows that consumers tend to give preference to brands that are committed to social and environmental responsibility. When Cause-Related Marketing is considered very influential, consumer buying interest tends to be high. The practical implication of this research is that companies can utilize CRM strategies as an effective tool to increase buying interest in their products and build more positive relationships with consumers. Further research can be conducted to understand other factors that influence the relationship between CRM and consumer purchasing interest in a broader context.